Influence of the hydrological regime on the water quality from the lake of the Francesa - Parintins/Amazonas/Brazil - Kimura, Solenise Pinto Rodrigues (Chemical Engineering Transactions, 2020)
The objective of this work was to evaluate the quality of the water from the lake of the Francesa in the city of Parintins/AM, taking into account the hydrological regime of the Amazon region. The study was based on analysis of the physiochemical parameters: temperature, pH, electrical conductivity, turbidity, suspended solids, dissolved oxygen, chemical and biochemical oxygen demand, total phosphorus, phosphate, total nitrogen, ammonia and nitrate. The collection periods covered the months of March and July of 2012 and 2013, totaling four collections. The results show that the lake receives a high load of urban wastewater, being evidenced in the high content of nutrients phosphorus, nitrogen compounds and expressive variation in the concentration of dissolved oxygen in the water level. Despite this, the lake has its own characteristics of environments with the ability to maintain the ecological balance in the period of greatest volume of water (July). © Copyright 2017, AIDIC Servizi S.r.l.